Pengembangan Aplikasi Android untuk Monitoring Suhu dan Kelembaban berbasis Internet of Things - Halim, William; Ardiani, Farida (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The easiest thing to determine whether a room is healthy or not is to know the temperature and humidity levels of the room. Therefore, it is necessary to monitor the temperature and humidity of the room at any time. From this, a design was created for a monitoring tool that can monitor room temperature and humidity based on the Internet of Things using Android Studio so that temperature and humidity can be monitored from anywhere and at any time. An Internet of Things (IoT) based room temperature and humidity monitoring tool was created using a NodeMCU ESP8266 and a DHT-11 Temperature Sensor and implemented using Android Studio. The Internet of Things (IoT) based room temperature and humidity monitoring process uses FIREBASE as a communication medium between the temperature sensor and NodeMCU with an Android device. Data from the temperature sensor connected to the NodeMCU is then forwarded to FIREBASE using topic publish. Androids who want to monitor temperature must subscribe to the published topic so they can get temperature and humidity data sent from the DHT-11 sensor. By utilizing this research, the public can make it easier to check temperature and humidity in real time with a smartphone or personal computer so that it can facilitate monitoring of the ideal temperature for baby rooms, farms, plants and so on in order to minimize anything undesirable.